Analisis Penerimaan Pajak Bumi dan Bangunan, Pajak Reklame dan Pajak Hiburan Pada Saat Masa Pandemi Covid-19 (Studi Pada Badan Pengelola Pajak Daerah Kota Palembang) - Windy Valentina; Yasir Arafat; Edduar Hendri (Universitas PGRI Palembang, 2022)
ABSTRACT This study aims to analyze how land and building tax revenues, advertisement taxes and entertainment taxes are received during the Covid-19 pandemic in Palembang City. The population used in this research is land and building tax revenue, advertisement tax and Palembang city entertainment tax. The sample technique used is a saturated sample where all members of the population are sampled, namely land and building tax revenues, advertisement taxes and entertainment taxes for the City of Palembang in 2019, 2020 and 202. The analytical method used in this study is descriptive qualitative. The results showed that at the beginning of the Covid-19 pandemic, namely in 2020, tax revenues decreased, both land and building tax revenues, advertisement taxes and entertainment taxes. However, in 2021 land and building tax receipts as well as advertisement taxes experienced a significant increase in revenue, except for entertainment tax revenues which continued to decline from 2020 to 2021. Keywords : land and building tax, advertisement tax, entertainment tax, Covid-19 Pandemic ABSTRAK Penelitian ini bertujuan untuk menganalisis bagaimana penerimaan pajak bumi & bangunan, pajak reklame & pajak hiburan pada saat masa pandemi Covid-19 di Kota Palembang. Populasi yang digunakan didalam penelitian ini ialah penerimaan pajak bumi & bangunan, pajak reklame & pajak hiburan Kota Palembang. Teknik sampel yang digunakan ialah sampel jenuh dimana semua anggota populasi dijadikan sampel yaitu penerimaan pajak bumi & bangunan, pajak reklame & pajak hiburan Kota Palembang tahun 2019, 2020 & 202. Metode analisis yang digunakan didalam penelitian ini ialah deskriptif kualitatif. Hasil penelitian menunjukkan bahwa pada awal pandemi Covid-19 yaitu tahun 2020 penerimaan pajak mengalami penurunan, baik penerimaan pajak bumi & bangunan, pajak reklame & pajak hiburan. Namun pada tahun 2021 penerimaan pajak bumi & bangunan serta pajak reklame mengalami peningkatan penerimaan yang cukup signifikan, kecuali penerimaan pajak hiburan yang terus mengalami penurunan dari tahun 2020 hingga tahun 2021. Kata Kunci: Pajak Bumi & Bangunan, Pajak Reklame, Pajak Hiburan, Pandemi Covid-19